NARCISSISTIC PERSONALITY TRAITS IN THE CONTEXT OF ACCOUNTING EDUCATION: AN APPLICATION OF THE ITEM RESPONSE THEORY - Lima Filho, Raimundo Nonato; Souza, Ariel Antônio Conceição de; D`Souza, Márcia Figueredo (Revista Universo Contábil, 2019)
This article aims to identify the manifestation of narcissistic personality traits in 187 students of Accounting from Northeast Brazil with the use of the Narcissistic Personality Inventory. Data were analyzed with the use of the Item Response Theory, the correlation analysis and the Student t test. Students showed prominent characteristics of authority and exhibitionism, with men and students of private institutions being more narcissistic. The results expand the restricted list of studies on narcissism in the national scene, seeking to contribute to discussions on the diagnosis of narcissistic personalities by educators, and to contribute to the improvement of educational processes.